PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA MODEL INKUIRI TERBIMBING SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KALOR DI SMA - Moh. Luqman Hakim; Prabowo Prabowo; Yuni Yuanita (JPPS (Jurnal Penelitian Pendidikan Sains), 2017)
The purpose of this research is produce physics learning material through guided inquiry model that valid, practical, and effective to improve learning outcomes of senior high school students. The development of learning material used the Kemp model and was tested X of SMA Hangtuah 1 Surabaya second semester in academic year 2013/2014 with One-Group Pretest-Posttest Design. Data of the study collected through observation, test, and questioner. The results of this research are: 1) Learning material developed has a valid category. 2) Learning material in terms of a practical category in feasibility of lesson plans and the students activities in accordance with steps of guided inquiry model. 3) The learning material effectiveness in terms of: (a) the increasing of students learning outcomes seen from exhaustiveness of indicator, individual, and classical; (b) the increasing of students comprehensiveness seen from high level of gain; (c) The students responds toward material and implementation of learning are very positive. Based on the findings of the study, Its conclusion that the learning material through guided inquiry model are valid, practical, and effective to increasing students' learning outcomes. It showed through the students' comprehensiveness of the concept, psychomotor skills and character, which are students' discipline and responsible. Penelitian ini bertujuan untuk menghasilkan perangkat pembelajaran fisika model inkuiri terbimbing yang valid, praktis, dan efektif sebagai upaya untuk meningkatkan hasil belajar siswa SMA. Pengembangan perangkat pembelajaran menggunakan model Kemp dan diujicobakan di kelas X SMA Hangtuah 1 Surabaya semester genap tahun ajaran 2013/2014 dengan One-Group Pretest-Posttest Design. Pengumpulan data menggunakan metode observasi, tes, dan angket. Temuan hasil penelitian, yaitu: 1) Perangkat pembelajaran yang dikembangkan berkategori valid; 2) Kepraktisan perangkat pembelajaran ditinjau dari keterlaksanaan RPP berkategori baik dan sesuai dengan tahap-tahap pada model inkuiri terbimbing; dan 3) Keefektifan perangkat pembelajaran ditinjau dari: (a) Peningkatan hasil belajar siswa terlihat dari ketuntasan indikator, individual, dan klasikal; (b) Peningkatan kemampuan pemahaman konsep siswa terlihat dari gain dengan kategori tinggi; dan (c) Respon siswa terhadap perangkat dan pelaksanaan pembelajaran sangat positif. Berdasarkan hasil temuan dalam penelitian ini, disimpulkan bahwa perangkat pembelajaran IPA Fisika dengan model inkuiri terbimbing, praktis dan efektif untuk meningkatkan hasil belajar siswa yang ditunjukkan oleh pemahaman konsep siswa, keterampilan psikomotor siswa, dan karakter siswa yang meliputi disiplin dan tanggung jawab siswa.